(untitled) (Biological Sciences - PJSIR, 2021)
This study aims to produce lipase of the Bacillus halodurans CM1 mutant and its assess partial characteristics, performed in Bora and Bora modified medium. The purification was conducted using Ultrafiltration (UF), ammonium sulfate (AS) and polyethylene glycol (PEG). Results revealed that the highest purity lipase of B. halodurans CM1 mutant was 1.49-fold from the UF-AS-dyalisis, with a molecular weight of 35.7-37.4 KDa. The optimum condition of lipase enzyme was achieved at pH 7 and temperature 50 °C, relatively stable at pH 7-8 and temperature 30-70 °C. Mg2+, Ca2+, Zn2+, Mn2+, Fe2+ and K+ ions of concentrations, 1 mM to 10 mM increased enzyme lipase activity. The Km value was 0.23 mg/mL and Vmax 4.07 U/mL. Lipase was stable with the addition of a detergent concentration of 1-2% (69.60-57.10%), and with the washing test, the enzyme capable of hydrolyzing oil on cloth is 8.40%.